Unscheduled Visits of Patients with Familial Melanoma to a Pigmented Lesion Clinic: Evaluation of Patients' Characteristics and Suspicious Lesions - Rania Nabil; Elsemieke Plasmeijer; Remco van Doorn; Wilma Bergman; Nicole A. Kukutsch (Medical Journals Sweden, 2018)
Approximately 10% of all melanomas occur in subjects with a family history of melanoma. This retrospective follow-up study investigated the characteristics of patients with familial melanoma who made unscheduled visits to our pigmented lesions clinic, and the diagnosis of excised lesions. A total of 110 (9%) out of 1,267 patients made at least one unscheduled visit between May 2011 and February 2016. Histopathology was taken from 59 patients. Thirty-four naevi, 7 melanomas and 3 basal cell carcinomas were detected. All patients with melanoma were CDKN2A carriers and all melanomas were discovered at a very early stage. In this patient population it appears to be safe to limit visits to once or twice yearly, provided patients are easily able to make an unscheduled extra visit if they have a worrisome lesion. We recommend supporting patients' self-reliance by stimulating them to carry out self-examination of their skin.